IMPLEMENTASI VIEWBOARD DALAM MENDUKUNG PENYEBARAN INFORMASI DENGAN PENYAJIAN ARTIFICIAL INFORMATICS PADA PERGURUAN TINGGI - Untung Rahardja; Deddy Pratama; Ely Susanti (CCIT Journal, 2016)
Information Technology (IT) has been able to made improve the effectiveness, efficiency, competitiveness, and support the managerial activities of the organization. Here are discussed about the implementation of Viewboard application for an educational institution as a module assistant of leadership in making strategic decisions. Viewboard applications developed based on existing databases on other systems as a data warehouse. In the implementation, the Viewboard applications built using the PHP programming language for the front-office interface with the concept of Artificial Informatics as a result of the processed grain database query. The Viewboard application has been tested for statistical measure of student overview on Higher Education Academic Raharja as a development and research Viewboard done. The final results show that the test can pull Viewboard processed data from an existing repository database and display the information is critical to the presentation of the characteristics of Artificial Informatics.